Mass Transfer Investigation of Liquid Membrane Transport of Gold (III) by Methyl Isobutyl Ketone Mobile Carrier - Kargari, A.; Kaghazchi, T.; Soleimani, M. (Chemical engineering & technology, 2004)
Extraction of AuIII ions by an emulsion liquid membrane (ELM) system with methyl isobutyl ketone (MIBK) as the mobile carrier and also liquid‐liquid extraction of AuIII from aqueous solutions have been studied. Experiments on the transport of the gold ions in a liquid‐liquid extraction system and stripping of the extracted ions from the organic phase as well as the extraction by a three‐phase W/O/W emulsion liquid membrane system have been performed. The results showed that even when the distribution coefficient of the diffusing species in the phases is small, the extraction by emulsion liquid membranes would be an effective process. A first‐order extraction rate was proposed and examined for the extraction system. Recently, liquid pertraction or liquid membranes appeared as a new and prospective separation method. Due to its advantages over solid membranes and liquid‐liquid extraction, it is at present the subject of intensive studies. Among the liquid pertraction systems, the emulsion liquid membrane (ELM) system is an effective technique for the extraction of solutes from aqueous or organic solutions. In this work, the extraction of AuIII ions by an ELM system with methyl isobutyl ketone as the mobile carrier as well as liquid‐liquid extraction of AuIII from aqueous solutions have been investigated.